2006
DOI: 10.3171/jns.2006.104.1.109
|View full text |Cite
|
Sign up to set email alerts
|

Influence of light fluence rate on the effects of photodynamic therapy in an orthotopic rat glioma model

Abstract: Treatment with ALA PDT induced pronounced necrosis in tumors only if the light was delivered at a low rate. The treatment prolonged the survival for tumor-bearing animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 43 publications
6
56
1
1
Order By: Relevance
“…Exogenous 5-ALA results in selective protoporphyrin IX (PpIX) accumulation in tumor cells including malignant gliomas to a greater extent compared to normal brain tissue [2][3][4][5][6]. 5-ALA induced fluorescence of PpIX, which has a maximum absorption around a wavelength of 400 nm, can be visualized by modified neurosurgical operating microscopes [7] and has shown to identify residual tumor during the resection of malignant gliomas in experimental and clinical settings [3,5,8].…”
Section: -Aminolevulinic Acid (5-ala) Is a Naturally Occurring Intermentioning
confidence: 99%
“…Exogenous 5-ALA results in selective protoporphyrin IX (PpIX) accumulation in tumor cells including malignant gliomas to a greater extent compared to normal brain tissue [2][3][4][5][6]. 5-ALA induced fluorescence of PpIX, which has a maximum absorption around a wavelength of 400 nm, can be visualized by modified neurosurgical operating microscopes [7] and has shown to identify residual tumor during the resection of malignant gliomas in experimental and clinical settings [3,5,8].…”
Section: -Aminolevulinic Acid (5-ala) Is a Naturally Occurring Intermentioning
confidence: 99%
“…Quite selective accumulation of 5-ALA-induced PP IX has been demonstrated for malignant glioma cells in vitro (23,24) and in vivo (25,26) as well as for many other tumour cells. In addition, due to the photosensitizing properties of PP IX, photodynamic treatment of malignant glioma might be considered as a promising additional therapeutic option, which is currently investigated in vitro (27,28) and in vivo (29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…In our study a total fluence dose of 15 J/cm 2 was chosen as we believed from preliminary experimentation that this dose would result in a sufficient PDT effect and the delivery of the total light dose at a fluence rate of 70 mW/cm 2 would be feasible for a "one-shot" intraoperative PDT treatment. In vitro studies have found PDT treatment with low fluence doses and low fluence rates to be more effective than low fluence doses with high fluence rates [36]. Finally, plates were measured for 'post' PpIX fluorescence levels (following light irradiation).…”
Section: Ppix Fluorescence Monitoring In Vitromentioning
confidence: 99%